Awareness towards social security protection among food delivery riders in Selangor and Kuala Lumpur / Nina Naquiah Ahmad Nizar ... [et al.] - Ahmad Nizar, Nina Naquiah; Ishak, Siti Zaharah; Shuib, Adibah; Wan Mohamed, Wan Mazlina; Sulaiman, Saiful Aman; Zainal, Mohd Irwanhakim; Taib, Mohd Nasir (Universiti Teknologi MARA, 2023)
Online food delivery services (OFDS) which are commonly endeavored by food delivery workers have become revolutionary today. However, the alarming rates of road accidents among them resulted in the announcement of obligatory contributions towards the Social Security Protection scheme in Malaysia, starting 1st October 2021. The Self-Employment Social Security Scheme was introduced to provide protection for individuals who are self-employed under the provisions of the Self-Employment Social Security Act 2017. A survey was conducted among 50 food delivery riders around Kuala Lumpur and Selangor on awareness of the scheme, exploring delivery rider demographic characteristics, awareness on benefits of the protection scheme, importance, or willingness to commit with the contribution towards social security protection, along with issues of concern during work. The analysis showed that the riders realize the importance and benefits of the Social Security Protection scheme and are willing to commit to it. Various underlying issues on egregious riding act to ensure fast delivery were also elaborated. In conclusion, the above findings provide evidence that food delivery riders understand that positioning them under the self-employment security scheme could provide protection against employment injuries including occupational diseases and accidents during work-related activities. Potential measures for a sound working environment and alleviate risky practices are also discussed.